THE HISTORY OF THE DEVELOPMENT OF THE NORMS OF THE CRIMINAL CODE PROVIDING FOR PUBLIC NECESSITY AND RESPONSIBILITY FOR INTERFERENCE IN INVESTIGATION OR CONSIDERATION OF CASES IN COURT IN UZBEKISTAN - Anorboev, Murodjon Rakhmankul Ugli (Educational Research in Universal Sciences, 2022)
This article discusses the social need to intervene in the interference in investigation or consideration of cases in court in Uzbekistan and the history of the development of the norms of the Criminal Code, for which liability is established. Chapter XVI of the Criminal Code of the current Republic of Uzbekistan is called "crimes against Justice", and in the theory of criminal law these crimes are highlighted as crimes that encroach on the normal functioning of bodies carrying out justice. According to the Constitution of the Republic of Uzbekistan, it is established that justice is carried out only by courts. Particular attention is paid to the fact that illegal interventions in the activities of investigative or judicial bodies are prohibited by law. As a result, theoretical and practical solutions for effective and short-term prevention of crimes of this category are proposed in Uzbekistan.